2019
DOI: 10.1186/s43044-019-0002-6
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular function outcome after coronary artery bypass grafting, King Abdullah Medical City (KAMC)- single-center experience

Abstract: BackgroundCoronary artery bypass grafting is known to be associated with better outcome in ischemic heart disease patients with low ejection fraction. We aim to demonstrate the effect of coronary artery bypass grafting (CABG) on left ventricle (LV) systolic function and to identify the predictors that adversely lead to postoperative poor outcome.ResultThis is a cross-sectional prospective study; we included 110 patients with left ventricular ejection fraction (LVEF) < 50% who underwent CABG with a mean age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
(27 reference statements)
3
7
0
Order By: Relevance
“…A male predominance was noticed (N = 138, 94.52%). The same results were seen in recent studies like Jose et al and Khalid et al [Jose 2019;Khaled 2019]. In Jose et al, it was 58.67 (9.70) years, and Khalid et al reported the same was 56.1 (12.2) years.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A male predominance was noticed (N = 138, 94.52%). The same results were seen in recent studies like Jose et al and Khalid et al [Jose 2019;Khaled 2019]. In Jose et al, it was 58.67 (9.70) years, and Khalid et al reported the same was 56.1 (12.2) years.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies worldwide have proven the relevance of CABG in left ventricular dysfunction [Jose 2019;Khaled 2019;Ngu 2018]. In ischemic cardiomyopathy, surgical revascularization helps to conserve the viable myocardium, reduce the ischemia, and help restore LV function.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac surgery outcomes improved in the past few years, and the current scoring systems are prone to overestimate poor outcomes. 12 Khaled et al 13 reported that CABG patients with low LVEF had acceptable mortality of 5.4%. Another study by Elassy et al 14 also found that LVEF < 35% was not a significant predictor of mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Complete revascularization is defined as an intervention targeting all stenotic coronary vessels with a diameter greater than >1.5mm and >50% lumen narrowing in at least one angiographic view and can be done with either percutaneous coronary intervention or CABG [Ong 2006]. Several studies support the role of CABG in improving EF in this patient category [Khaled 2019;Koene 2017].…”
Section: Discussionmentioning
confidence: 99%
“…The patients were classified into two groups: group I, 76 (69%) patients with EF > 35%, and group II, 34 (31%) patients with EF < 35%. Both groups had a significant postoperative EF increase with an average EF of 29.76 ± 4.868 pre-CABG to 33.53 ± 9.655 postoperative (P < 0.05) [Khaled 2019]. This increase in EF is perhaps due to revascularization of hibernating myocardium caused by chronic low blood flow circulating the myocardium [Kloner 2020].…”
Section: Discussionmentioning
confidence: 99%